A review on using thermoelectric cooling, heating, and electricity generators in solar energy applications. (August 2022) - Shoeibi, Shahin; Kargarsharifabad, Hadi; Sadi, Meisam; Arabkoohsar, Ahmad; Mirjalily, Seyed Ali Agha
Highlights: TEC, TEH and TEG increase the performance of solar stills. The highest increased water yield is obtained in solar still using TEC and TEH. The power generation in solar chimney with TEG is very low. Using nanofluid and TEG has high effect on electrical efficiency of PV panel. Tubular TEG connected to solar water heater rises the power output up to 161.7 W. Abstract: Parallel with the rapid advances of solar technologies as the very crucial components of future energy systems, much interest has also been observed in scientists and commercial companies for the further development and use of thermoelectric systems during recent years. This has led to an interesting field of research combining solar systems/technologies and thermoelectric systems for a variety of purposes. Thermoelectric cooling, heating, and power generators are here proposed in different ways to enhance the performance of solar energy systems. In thermoelectric heating applications, the hot side of the thermoelectric module contributes to increasing the temperature of the solar working fluid in e.g. the desalination, water or air heater systems, etc. For the thermoelectric cooling case, the cold side of the module plays a supplementary or main role in reducing the temperature of e.g. PV panels, the condensation area of desalination units, etc. A thermoelectric power generator may be used to convert the waste thermal energy or the main heat flow output of a solar system to electricity. A combination of heating, cooling, and/or electricity generating thermoelectric units in solar systems could also be frequently seen in the literature. This article, presenting a summary and discussion of previous articles published recently in the literature, aims to make a review and assessment of the methods and impacts of thermoelectric devices on the performance of solar systems in various designs, and thereby, giving readers a good insight into the state-of-the-art and the gaps.